Trends in mobile technology-supported collaborative learning: A systematic review of journal publications from 2007 to 2016. (April 2018) - Fu, Qing-Ke; Hwang, Gwo-Jen
Abstract: This study reviewed the literature on mobile technology-supported collaborative learning from 2007 to 2016. Several issues, such as the distributions and research methods, learning devices and learning environments, participants, research issues, application domains, grouping methods and collaborative learning strategies, are addressed. In addition, the relationship between the learning strategies and measurement issues are investigated. The review found that the amount of research on mobile collaborative learning increased and the connection between new mobile technology and collaborative learning activities became tighter. College students received the greatest emphasis, but more focus should be put on junior and elementary school students. Few studies were conducted on teachers and adults. In the most recent five years, the research was focused on improving learners' performance in science, especially social science, and in natural scenarios outside of the classroom, but less emphasis was put on developing learners' skills and higher order skills. There was little research focusing on different selection methods of group members and the teaching effects of grouping design. Most research adopted conceptualized collaborative learning strategies. Furthermore, some studies proposed that the collaborative learning activities conducted in mobile learning environments should be designed carefully to guide students to experience more effective collaborative constructivist learning. Based on the findings, in-depth discussion and suggestions for future studies are given. Highlights: A systematic review on collaborative m-learning from 2007 to 2016 is conducted. Several issues (i.e., topics, learning strategies and grouping methods) are addressed. The relationship between learning strategies and measurement issues are investigated The findings are discussed in depth Suggestions for future studies are given based on the findings